2018
DOI: 10.1371/journal.pone.0203485
|View full text |Cite
|
Sign up to set email alerts
|

Short-term low salinity mitigates effects of oil and dispersant on juvenile eastern oysters: A laboratory experiment with implications for oil spill response activities

Abstract: Following the Deepwater Horizon oil spill, eastern oyster (Crassostrea virginica) reefs in the northern Gulf of Mexico were exposed to oil and various associated clean-up activities that may have compromised oyster reef health. Included in the exposure was oil, dispersant, and in some locales, atypical salinity regimes. Oil and dispersants can be detrimental to oysters and the effects of salinity depend on the level. In addition to these extrinsic factors, genetic diversity of oyster populations may help the o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 47 publications
0
11
0
Order By: Relevance
“…While oysters have substantialtolerance for varying salinity and temperature regimes (Sehlinger et al, 2019), prolonged exposure to low salinities of <5 ppt will eventually result in death (Powers et al, 2017a). Schrandt et al (2018) in fact demonstrated that in laboratory conditions, short-term episodes of low salinity water may mitigate effects of oil/dispersant exposures. However, longterm fresh water conditions persisted in Breton Sound/Black Bay and Barataria Bay in much of the spring and summer of 2010, likely resulting in excess mortalities of 1.16-3.29 billion market sized oysters due to low salinity stress (Powers et al, 2017a).…”
Section: Species-level Summariesmentioning
confidence: 99%
“…While oysters have substantialtolerance for varying salinity and temperature regimes (Sehlinger et al, 2019), prolonged exposure to low salinities of <5 ppt will eventually result in death (Powers et al, 2017a). Schrandt et al (2018) in fact demonstrated that in laboratory conditions, short-term episodes of low salinity water may mitigate effects of oil/dispersant exposures. However, longterm fresh water conditions persisted in Breton Sound/Black Bay and Barataria Bay in much of the spring and summer of 2010, likely resulting in excess mortalities of 1.16-3.29 billion market sized oysters due to low salinity stress (Powers et al, 2017a).…”
Section: Species-level Summariesmentioning
confidence: 99%
“…The summer release of large quantities of freshwater from the Mississippi River through the Caernarvon and Davis Pond diversion structures as the State of Louisiana moved to protect marsh ecosystems from the inflow of oil in 2010 resulted in the loss of 2-3 billion market-sized oysters from subtidal areas of Barataria Bay and Black Bay/Breton Sound estuaries (Grabowski et al, 2017;Powers et al, 2017b). Mesocosm experiments funded by GoMRI indicated that exposing oysters to short periods of low salinity could help them combat oil contaminant effects; however, this must be balanced by heavy expected mortality resulting from extended periods at very low salinity (Schrandt et al, 2018). Oysters near the shoreline (fringing oyster reefs) suffered injury from direct oiling as well as from oil removal efforts (Powers et al, 2017a).…”
Section: Oyster Restoration and Recoverymentioning
confidence: 99%
“…It is made The copyright holder for this preprint this version posted February 15, 2021. ; https://doi.org/10.1101/2021.02.15.431248 doi: bioRxiv preprint public leases were delayed east of the Mississippi River in 2010 due to a depressed spat set and oyster mortalities [16]. In addition, dramatic density decreases of oysters in areas affected by freshwater diversion efforts have been documented [17,18], although in experimental work, Schrandt et al [19] found that lower salinity conditions (5-10 ppt) led to increased survival of juvenile C. virginica exposed to oil and dispersed oil. In addition, Dietl and Durham [20] did not detect any significant difference of adult shell size between a baseline of pre-spill historical specimens and those collected in the years 2011 to 2013.…”
Section: Plosmentioning
confidence: 99%